Analisis Kandungan Total Padatan Terlarut dan Sensori Sari Buah Lemon Cina (Citrus microcarpa) - Thenu, Silvia; Tetelepta, Gilian; Ega, La (Universitas Pattimura, 2023)
The purpose of this study was to determine the optimal fruit juice-to-water ratio for producing lemon cina with best chemical and organoleptic properties. This study utilised a completely randomized design with one factor, the ratio of fruit juice to water, and five treatment levels, namely 1:3, 1:4, 1:5, 1:6, and 1:7. Total dissolver solids and sensory including color, aroma, and taste were analysed as parameters. Lemon cina juice with a fruit juice-to-water ratio of 1:4 was the optimal treatment with a TPT of 42oBrix, whereas for hedonic quality, the juice had a colour of 2.32 (slightly yellow), an aroma of 2.72 (close to citrus lemon cina), and a taste of 3.04 (lemon cina taste).